1995
DOI: 10.1364/ol.20.000982
|View full text |Cite
|
Sign up to set email alerts
|

Efficient low-intensity optical phase conjugation based on coherent population trapping in sodium

Abstract: We have observed optical phase-conjugate gain (.50) in sodium vapor, using low-intensity pump lasers (1 W͞cm 2), with a response time of the order of 1 ms. Coherent population trapping is experimentally identified as the phase-conjugate mechanism. A theoretical model is presented that supports these observations by showing that coherent population trapping can write large-amplitude nonlinear-optical gratings at laser intensities well below those needed to saturate the optical transitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
189
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(197 citation statements)
references
References 20 publications
(19 reference statements)
2
189
1
Order By: Relevance
“…Second, although the present work demonstrates stationary light localization and storage in one dimension, it should be possible to controllably localize and guide stationary photonic pulses in three spatial dimensions by using control beams with properly designed wavefronts. Third, controlled conversion of propagating light into stationary light pulses opens interesting possibilities for enhanced nonlinear optical processes by combining the present technique with the resonant enhancement of nonlinear optics via EIT [24][25][26] . This combination may enable controlled interactions involving quantum few-photon fields [27][28][29][30] analogous to those feasible in cavity quantum electrodynamics 5 .…”
mentioning
confidence: 95%
“…Second, although the present work demonstrates stationary light localization and storage in one dimension, it should be possible to controllably localize and guide stationary photonic pulses in three spatial dimensions by using control beams with properly designed wavefronts. Third, controlled conversion of propagating light into stationary light pulses opens interesting possibilities for enhanced nonlinear optical processes by combining the present technique with the resonant enhancement of nonlinear optics via EIT [24][25][26] . This combination may enable controlled interactions involving quantum few-photon fields [27][28][29][30] analogous to those feasible in cavity quantum electrodynamics 5 .…”
mentioning
confidence: 95%
“…The work of the past few years has shown that substantial improvements in resonant nonlinear optics can be achieved by utilizing the concepts of quantum coherence and interference [4,5]. The aim of the present contribution is to demonstrate the usefulness of this regime of nonlinear optical enhancement for applications involving quantum correlations and reduction of quantum noise.…”
mentioning
confidence: 92%
“…However, the efforts to exploit these properties were hindered, either by the small values of nonlinearities in available optical crystals, or by absorption losses and the associated noise in resonant atomic systems with large nonlinearities. For example, four-wave mixing is known to result, in principle, in squeezed-state generation or non-classical correlations [2], but all experimental realizations reported to date showed rather limited noise reduction and required the use of cavities [3].The work of the past few years has shown that substantial improvements in resonant nonlinear optics can be achieved by utilizing the concepts of quantum coherence and interference [4,5]. The aim of the present contribution is to demonstrate the usefulness of this regime of nonlinear optical enhancement for applications involving quantum correlations and reduction of quantum noise.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One particularly interesting nonlinear process based on EIT is the resonantly enhanced 4-wave mixing in a double-Λ system with counter-propagating pump modes [9]. It has been shown experimentally [10] and theoretically [11,12] that this system can show a phase transition to mirrorless oscillations for rather low pump powers.…”
Section: Introductionmentioning
confidence: 99%